PERTUMBUHAN DAN PRODUKSI DUA VARIETAS TANAMAN TERUNG (Solanum melongena L.) YANG DIBERI PUPUK KOMPOS KANDANG SAPI - Silalahi, Saur Madan; Hamzah, Anthony (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
This research aims to obtain doses of cow manure compost in increasing the growth and production of eggplant varieties Mustang F1 and Yuvita F1. This research was conducted in the experimental garden of the Faculty of Agriculture, University of Riau, Campus Bina Widya Km 12.5 Simpang Baru, Tampan Subdistrict Pekanbaru District and lasts for three months starting in March 2019 until June 2019. This research was conducted experimentally by using a randomized plot design divided into randomized groups consisting of 2 factors and 3 replications. The main plot is cow manure compost which consists of 4 levels (cow manure compost doses of 0, 75, 150, and 225 g per crop).  The parameters observed were soil analysis, plant height, stem diameter, number of leaves, age of flowering, first harvest age, number of fruits per crop, fruit length, fruit diameter, fruit weight per plant and fruit weight per plot. The data obtained were statistically analyzed with diversity followed by Duncan's multiple range test at the 5% level. The results showed that increasing the dose of cow manure compost 75 g per plant to 225 g per plant given was not significantly different for all observation parameters the distinction is in crop height parameters without using cow manure compost. Keywords: Eggplant, Mustang F1, Yuvita F1 and manure storage cow shed